Frequency effects and the processing of verbal morphology by L1 and L2 speakers of english - Baltazar, Laura Mesquita (2012)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente, Florianópolis, 2012